Makna Simbolik Ritual Pengobatan Tetomeh Di Desa Sintong Kabupaten Rokan Hilir - Sari, Nova Serliana; Yozani, Ringgo Eldapi; ., Elmustian (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study aims to understand the symbolic meanings embedded in the Tetomeh ritual and how these symbols are constructed and interpreted by the people of Sintong Village through social interaction. The symbolic interactionism theory is used to examine both verbal and nonverbal communication within the ritual, including chants, prayers, and bodily expressions performed by the shaman as an intermediary between humans and supernatural entities. A qualitative research method with a communication ethnography approach is applied, with data collected through in-depth interviews, observation, and documentation. The findings indicate that the symbols in the Tetomeh ritual function not only as tools for healing but also as a medium for cultural transmission that reinforces the relationship between humans, nature, and the spiritual realm. This ritual plays a significant role in preserving traditional values and strengthening social bonds within the Sintong Village community.